Analisis Portofolio Sumber Dana PT Bank X Sebagai Instrumen Optimalisasi Budgeting dan Pengambilan Strategi - Putra, Yudha Pradipta; Dewi, Farida Ratna (IPB University, 2010)
The rising of credit expansion by PT Bank X has an implication to the high needs of fund. The fund source of PT Bank X derived from third party fund account and transfer fund among offices. Every funding source has advantages, disadvantages and cost which must be examined because it can affect the bank’s income. The purposes of this research are: (1) to identify the funding structure of PT Bank X, (2) to analyze the effect of every funding source to the PT Bank X, and (3) to analyze how the portfolio funding structure can be used to the budgeting process and strategy formulation. The funding source of PT Bank X consists of third party fund account and transfer fund among offices. In 2005-2007 period, transfer fund among offices gave the biggest contribution in the funding source portfolio. The demand deposit gave the biggest impact in the income. Saving deposit also gave the positive affect and significant. The cost of saving deposit is quite low. Although demand deposit and saving deposit are included as the unstable fund in the asset portfolio of PT Bank X, the potential and the growth level which are very high can help PT Bank X to provide fund with low cost. Interest from the use of transfer fund among offices is quite big that give the negative impact to the income.